2020
DOI: 10.1039/d0cp01814g
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles influence miscibility in LCST polymer blends: from fundamental perspective to current applications

Abstract: Polymer blending is an effective method which can be used to fabricate new versatile materials with enhanced properties. Blending of two polymers can either result in a miscible or immiscible...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 143 publications
0
9
0
Order By: Relevance
“…46 The smaller size of NPs compared to the radius of gyration of the PVDF polymer enhances the polymer−NPs interaction and lowers the mixing enthalpy due to the low polymer−polymer chain interface. 47 From Figure 1a, it is observed that the average size of ZnO NPs is ca. ∼20 nm, which is smaller than the radius of gyration of the PVDF polymer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…46 The smaller size of NPs compared to the radius of gyration of the PVDF polymer enhances the polymer−NPs interaction and lowers the mixing enthalpy due to the low polymer−polymer chain interface. 47 From Figure 1a, it is observed that the average size of ZnO NPs is ca. ∼20 nm, which is smaller than the radius of gyration of the PVDF polymer.…”
Section: Resultsmentioning
confidence: 99%
“…They showed that the polymer swells if the NPs are properly dispersed and the size is less than the radius of gyration R g of PVDF (∼27.5 nm) . The smaller size of NPs compared to the radius of gyration of the PVDF polymer enhances the polymer–NPs interaction and lowers the mixing enthalpy due to the low polymer–polymer chain interface . From Figure a, it is observed that the average size of ZnO NPs is ca.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Polymeric materials are now more widely used than steel and ceramics owing to their low cost, ease of processability, and rust resistance. 1,2 The main drawback of polymer-based materials is that they are prone to UV damage from various sources. Inferior resistance to UV radiation may limit their use in applications such as packaging.…”
Section: Introductionmentioning
confidence: 99%
“…After obtaining a consistent MFI in the mixed plastics, the next objective is to improve their interfacial adhesion. Polymers can either be partially miscible or immiscible, depending on their interaction at the interface. Many polymers are immiscible, which limits their applications due to their poor mechanical properties. This issue can be resolved by adding various types of compatibilizers to enhance the interfacial adhesion between the different polymers. , For example, polymer-grafted maleic anhydride compatibilizers have been used to improve the mechanical properties of different types of polymer systems …”
Section: Introductionmentioning
confidence: 99%